Effect of Relative Humidity on Tribological and Mechanical Properties of PA6-Based Composites - Baráth Martin; Kotus Martin; Boszorádová Lucia; Baláži Juraj; Hrabovský Leopold; Pravda Štěpán (Management Systems in Production Engineering)
The article examines how relative humidity affects the wear resistance and mechanical properties of PA6, PA6 GF30, and Onyx, processed by 3D printing. Findings show that mass loss rises with humidity across all materials, with Onyx exhibiting the lowest average mass loss despite larger percentage increases. At pressure value of 0.32 N·mm-2, mass loss increased due to their properties compared to metallic materials by 2.4% from 33% to 65% humidity, then by 10.5% from 65% to 97%. Notably, at high humidity, there were significant differences in wear loss between parallel and vertical orientations, with Onyx showing a 36% difference at 97% humidity. Tensile tests revealed a strong correlation between humidity and tensile strength in PA6 of 0.9331 correlation coefficient value, while PA6 GF30 showed inconsistent properties. For Onyx, higher humidity led to substantial drops in tensile strength (0.911 correlation coefficient value) and increases in elongation (0.603 correlation coefficient value). The contribution of this study lies in its ability to guide the selection of composite materials, for wet and abrasive conditions, optimizing wear resistance and extending component lifespan while reducing maintenance needs.